Multilingualism, collaboration and experiential learning with multiple modalities: the case of Mondovision. Issue 4 (7th August 2020) - Ivković, Dejan
ABSTRACT: The paper documents the final project in an undergraduate seminar on multilingualism at the University of Toronto from a pedagogical perspective. The multimodal and multimedia project – centered on the idea of a fictitious festival of popular music, the Mondovision Song Contest – uses the genre of pseudo-documentary as a channel for collaborative and experiential learning. The students get engaged in multiple roles: script writer, graphic designer, film editor, actor/actress, and dancer, to mention a few. The Mondovision project serves as a medium to not only master subject matter content that focuses on multilingualism across continents, but also gives the students an opportunity to develop interpersonal and collaboration skills and to acquire multimedia and multimodal literacies. The paper provides both student and instructor perspectives on the experience, focusing on their respective roles and exemplifying what is here referred to as affirmative pedagogy of multilingualism .